AQP5 trafficking is regulated by its C-terminal tail and interaction with prolactin-inducible protein - Claudia D’Agostino; Egor Zindy; Louise Conrard; Amel Takkal; Françoise Gregoire; Nargis Bolaky; Susanna Törnroth-Horsefield; Jason Perret; Christine Delporte (Biology Direct)
Abstract Background Aquaporin-5 (AQP5) is a crucial membrane protein involved in water transport across cellular membranes, particularly within exocrine glands such as salivary glands. Dysregulation of AQP5, including its mislocalization, has been associated with various diseases, emphasizing the need to understand the molecular mechanisms governing its trafficking. This study investigates the multifaceted regulatory mechanisms of AQP5 trafficking, with specific emphasis on the role of the carboxyl-terminal (C-terminal) tail and the functional involvement of prolactin-inducible protein (PIP) as an interacting protein partner. Methods An innovative 2D-custom model employing SNAP-tag human AQP5 constructs together with a novel automated algorithm-based methodology was used following immunofluorescence and confocal microscopy to assess hAQP5 localization to the plasma membrane of stably transfected normal salivary gland-SV40 transformed-acinar cells (NS-SV-AC). The expression of the constructs was verified by Western blot analysis. Results The expression of SNAP-hAQP5 constructs expressed in stably transfected NS-SV-AC cells allowed to explore the involvement of hAQP5 C-terminal tail and the hAQP5-hPIP interaction in hAQP5 trafficking upon stimulation. The use of C-terminal truncation constructs revealed distinct responses to intracellular 3’,5’-cyclic adenosine monophosphate (cAMP) and calcium increase, shedding light on the importance of specific regions within the highly flexible distal part of the C-terminal tail for AQP5 trafficking. Furthermore, our investigation of the interplay between hAQP5 and hPIP revealed that PIP promotes AQP5 translocation to the plasma membrane, blunting the effects of calcium- and cAMP-dependent pathways on AQP5 sub-cellular localization. Conclusion In summary, this study advances our understanding of AQP5 trafficking dynamics and provides critical insights into the regulatory roles of the C-terminal tail and its interaction with PIP. The innovative methodology to assess AQP5 translocation to the plasma membrane sets the stage for future investigations to identify the role of individual amino acids and phosphorylation sites within the distal AQP5 C-terminus in the trafficking mechanism and protein-protein interaction, and to explore the dynamic of the process by high resolution live cell imaging. Further research in this area is warranted to uncover critical insights into the regulation of AQP5, offering opportunities for the development of innovative therapeutic strategies.